2014
DOI: 10.1007/s12550-014-0203-5
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a comprehensive definition of modified and other forms of mycotoxins including “masked” mycotoxins

Abstract: As the term “masked mycotoxins” encompasses only conjugated mycotoxins generated by plants and no other possible forms of mycotoxins and their modifications, we hereby propose for all these forms a systematic definition consisting of four hierarchic levels. The highest level differentiates the free and unmodified forms of mycotoxins from those being matrix-associated and from those being modified in their chemical structure. The following lower levels further differentiate, in particular, “modified mycotoxins”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
209
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(221 citation statements)
references
References 59 publications
3
209
0
9
Order By: Relevance
“…Metabolisation of mycotoxins in planta yields so called 'masked' mycotoxins, which are not routinely analyzed, but remain hazardous since endogenous hydrolases may cleave the compound and reactivate the toxin (Rychlik et al 2014). Several conjugated forms of DON such as DON-3-glucoside (Poppenberger et al 2003) and DON sulfates (Warth et al 2015), but also of zearalenone and fumonisins have been identified to date (De Saeger and Van Egmond 2012;Berthiller et al 2013).…”
Section: The Masked Mycotoxin Problemmentioning
confidence: 99%
“…Metabolisation of mycotoxins in planta yields so called 'masked' mycotoxins, which are not routinely analyzed, but remain hazardous since endogenous hydrolases may cleave the compound and reactivate the toxin (Rychlik et al 2014). Several conjugated forms of DON such as DON-3-glucoside (Poppenberger et al 2003) and DON sulfates (Warth et al 2015), but also of zearalenone and fumonisins have been identified to date (De Saeger and Van Egmond 2012;Berthiller et al 2013).…”
Section: The Masked Mycotoxin Problemmentioning
confidence: 99%
“…After more than a decade, soluble and insoluble conjugates of mycotoxins that can be formed upon chemical or biochemical reaction fall under the umbrella of this definition. A tentative comprehensive classification is reported in Figure 5, mainly based on the mechanism of masking (modified from Rychlik et al, 2014). Compounds deriving from chemical reactions occurring upon processing, as described in Section 8.4, are also reported in the figure. EFSA Journal 2014;12(12):3916 26 Modified mycotoxins are mainly produced by plants via enzymatic transformations related to detoxification processes (phase II metabolites) and have been related to a resistance mechanism exerted by plants to counteract pathogen invasion Berthiller et al, 2007Berthiller et al, , 2013.…”
Section: Natural Occurrence and Environmental Fatementioning
confidence: 99%
“…They can chemically modify mycotoxins or compartmentalize them to a less toxic form [58]. For example, deoxynivalenol-3-glucoside (D3G) is a product of a detoxifying plant mechanism, where DON is subjected to glycosylation via a different conjugation reaction [58,59]. The plant modification system has been thoroughly described in a review by Berthiller et al [58].…”
Section: Fungal Toxins In Malting and Brewingmentioning
confidence: 99%